The effect of gendarussa vulgaris methanolic extract on the reproductive organs of female mice - Wan Zakaria, Wan Nurhakimah (2015)
Gendarussa vulgaris (GV) (syn. Justicia gendarussa) is locally known as gandarusa or daun rusa in Malay. This plant belongs to Acanthaceae family and is commonly found in tropical Asian regions including Malaysia. This plant is traditionally being used to treat fever, bone fracture, rheumatism, arthritis and muscle pain, and amongst others. The plant has been proven to have antibacterial, antiparasitic, antinociceptive, antioxidant, antiangiogenic, anti-inflammatory, antiviral and antitumor properties. Moreover, the leaves of the plant in the form of pills are commercially being used in Indonesia as contraceptive agent in men. Gendarusin A and B that are present in the plant have been shown to induce sterility in vitro by preventing penetration of sperm into the ovum. However, the effect of the plant on the female reproductive organs is still unknown. This study embarks on the effect of plant on the reproductive organs of female mice. Gendarussa vulgaris methanolic extract (GVME) was prepared from the mature leaves collected from its natural habitat in Kulim, Kedah. A total of 24 mice (n=8) were divided into 3 groups. The positive control group was treated with 0.35mg/kg clomiphene citrate; the negative control group was treated with 0.9% NaCl at 10ml/kg bodyweight while the third group was treated with 300mg/kg GVME (p.o.) once daily for 10 days. Behaviour of mice in each group such as feeding and drinking, defecating and urinating, restlessness, loss/reduce mobility, abnormal resting posture, unresponsiveness, failure to groom/unkempt appearance, licking, biting, scratching or shaking, mortality, pain upon restraining and body weight changes were observed during the treatment period. At the end of the treatment period, mice were euthanised and their reproductive organs were harvested. No abnormal behavioural changes or mortality were observed during the treatment period . The results were not significantly different p<0.05 for the body weight changes for all the 3 groups. Results for the lesion scoring showed no significant difference for congestion and granulosa cell abnormality of the right ovary, left ovary and congestion in uterus between control groups and treatment group at p<0.05. The liver and kidney congestion and kidney necrosis showed no significant difference at p<0.05. However, the lesion score of uterine inflammation between groups and within groups showed significant difference at p<0.05. The lesion score for the liver necrosis is significantly different between control groups and treatment group at p<0.05. The function of the female reproductive system may be assessed by monitoring the pregnancy rate and the percentage of abnormality among the newborns. Furthermore, treatment using different extracts such as ethanol and aqueous should be conducted to compare the effects of these 2 extracts on the reproductive system, as different extract possess different bioactive compounds. The assessment of the reproductive function may also be done by measuring the levels of the reproductive hormones produced at pre- and post-treatment periods. Finally, the health status of the mice need to be determined to ensure that the mice used for the study are healthy to avoid unintentional observational bias.